Assessment Of Factors Affecting Cash Management Activities- Experimental Study In Listed Textile Enterprises (Journal of Namibian Studies : History Politics Culture, 2023)
Objective: The study analyzes the impact of factors on profitability of cash flow management enterprises of textile and garment enterprises listed on Vietnam stock exchange - VNX (HNX, HoSE and Upcom).Theoretical framework: domestic and foreign studies related to cash flow management activities.Method: using Qualitative Research (Synthetic Methods; Statistical methods, description; Inductive and interpretive methods) and quantitative research methods (FEM, REM).Results and conclusion: The author has identified independent variables affecting cash flow management of listed textile enterprises, including: receivables from customers, inventory, payables to sellers, and size of the business. In addition, the control variables: growth opportunities of enterprises, economic environment are not statistically significant.Implications of the research: The experimental results are the basis for the authors to make recommendations to improve the efficiency of cash flow management in listed textile enterprises in the coming time.Originality/value: Research to help managers of listed textile enterprises come up with appropriate solutions for optimal cash flow management.